The Second Deep Ice Coring at Dome Fuji, Antarctica. - Hideaki Motoyama; Akiyoshi Takahashi; Yoichi Tanaka; Kunio Shinbori; Morihiro Miyahara; Takayasu Yoshimoto; Yoshiyuki Fujii; Toshitaka Suzuki; Teruo Furukawa; Kumiko Goto-Azuma; Keisuke Suzuki; Atsuhiro Muto; et al. (National Institute of Polar Research, 2020)
The second deep ice coring project was carried out at Dome Fuji, Antarctica. Following the pilot hole drilling in 2001, deep ice core drilling was conducted for four years from the 2003/2004 austral summer season, reaching a depth of 3035.22 m in January 2007. The drilling was performed only in the summer season. Therefore, many improvements were made to the problems of the first deep ice core drilling system to enable efficient drilling. In particular, the core length that can be obtained at one time was increased from 2.3m to 3.84 m, and the chip storage efficiency was enhanced. In this report, the outline of the drilling system, the method of drilling, the progress of drilling operation, and various troubles were reported. Also, future issues are indicated.